SYNTHESIS OF CHITOSAN-MAGNETITE NANOPARTICLES CROSS-LINKED TRIPOLYPHOSPHATE AS ANTIBACTERIAL Salmonella typhi AND Staphylococcus aureus - Mahyati, Agus; Koesnarpadi, Soerja; -, Erwin (JURNAL ATOMIK, 2021)
Magnetite is widely used in various fields of separation, biochemistry, medical and environment. Modification of nanoparticle magnetite binding with chitosan is recommended for many biomedical applications, especially as a drug delivery system because in addition to its non-toxic, biodegradable and biocompatible characteristics. Another advantage of biomedical benefits as antimicrobial is that it can increase antibacterial activity and has a more pronounced effect on gram-negative and gram-positive bacteria. Synthesis and characterization of chitosan-magnetite cross-linked tripolyphosphate as an antibacterial of S. typhi (Gram negative) and S. aureus (Gram positive) has been carried out. The phase of this research was initiated by the synthesis of FeSO4.7H2O and FeCl3.6H2O magnetite with a mass ratio of Fe (II): Fe (III) = 2: 3, using the co-precipitation method. In the second stage where the cross-linking of chitosan with TPP cross-linker to form ferrogel. In the third stage the synthesis of TPP-chitosan-magnetite in a ratio of 1: 4, with a slight addition of NH4OH as participant material. The results showed that FT-IR on TPP-chitosan-magnetite has a unique spectrum, XRD results showed the crystal structure of TPP-chitosan-magnetite did not change. Surface morphology shows that TPP-chitosan-magnetite is a spherical surface. Chitosan-Magnetite material has greater antibacterial activity than chitosan and magnetite bacteria S. typhi (Gram negative) and S. aureus (Gram positive).